Nowcasting Norwegian GDP: The Role of Asset Prices in a Small Open Economy - Knut Are Aastveit; Tørres G. Trovik (Norges Bank, 2007)
This paper finds that asset prices on Oslo Stock Exchange is the single most important block of data to improve estimates of current quarter GDP in Norway. Other important blocks of data are labor market data and industrial production indicators. We use an approximate dynamic factor model that is able to handle new information as it is released, thus the marginal impact on mean square nowcasting error can be studied for a large number of variables. We use a panel of 148 non-synchronous variables covering a broad spectrum of the Norwegian economy. The strong impact from financial data is due to an ability of the market clearing process to impart information about the real activity in Norway in a timely manner.
hdl:11250/2498265
Keywords: E37; E50; G14; 330; forecasting; financial markets; economic growth; small open economy